Sociological Approach to Eradication Corruption in Indonesia (Alternative to Imprisonment) - Muhammad Ali Zaidan (Universitas Negeri Semarang, 2019)
Punishment of corruption not quite put in the context of law enforcement, leading to sanctions of imprisonment. Reality shows more than 600 state officials have been convicted of corruption but the rate has no effect at all to prevent the corruption. If no breakthrough is the law, the state can be called a defeat and to its knees at the foot of criminals. As a result, Indonesia can be called a heaven for criminals country. As a rule of law, law enforcement must be done in a holistic and integrated. Thus the imprisonment should also be offset by imposing sanction corrupt social order to be cured/deterrent. Make criminals real deterrent is not an easy step, but in need of understanding and synergy between the law enforcement community on the one hand with the other hand to continue to spread the spirit of corruption eradication in all social strata. The imposition of sanctions of imprisonment must also be followed by removal of political rights, especially the right to have occupied political positions both in government agencies and representatives (DPR). Sanctioning the disenfranchisement of political rights for a time after undergoing convict prison, is a powerful tool and a non-penal nature to combat corruption.